Policy design labs and uncertainty: can they innovate, and retain and circulate learning? - Jenny M. Lewis (Policy Design and Practice)
Around the world in recent times, numerous policy design labs have been established, related to a rising focus on the need for public sector innovation. These labs are a response to the challenging nature of many societal problems and often have a purpose of navigating uncertainty. They do this by “labbing” ill-structured problems through moving them into an experimental environment, outside of traditional government structures, and using a design-for-policy approach. Labs can, therefore, be considered as a particular type of procedural policy tool, used in attempts to change how policy is formulated and implemented to address uncertainty. This paper considers the role of policy design labs in learning and explores the broader governance context they are embedded within. It examines whether labs have the capacity to innovate and also retain and circulate learning to other policy actors. It argues that labs have considerable potential to change the spaces of policymaking at the micro level and innovate, but for learning to be kept rather than lost, innovation needs to be institutionalized in governing structures at higher levels.